The Magnitude of Hepatic Transaminase Rise and Its Correlation with the Severity of Dengue Fever (BIRDEM Medical Journal, 2016)
Background and Objective: Biochemical evidence of hepatic enzyme rise is very common in dengue fever. This study was designed to see the levels of elevated hepatic enzymes and their correlation with severity of dengue fever (DF).\Materials and Methods: It was an observational study conducted in the Department of Internal Medicine of BIRDEM Hospital, Dhaka, over a period of six months (July to December, 2010). Fifty serologically confirmed (IgM/IgM and IgG) dengue fever patients were included in the study.Results: Of the 50 patients, 32 (64%) were male and 18 (36%) were female. The mean age was 44.2 (21-54) years. Out of 50 cases, 23 (46%) cases had classical dengue fever, 20 (40%) had dengue haemorrhagic fever (DHF) Grade I, 6 (12%) had DHF Grade II and 1 (2%) had DHF Grade III. Hepatic enzymes were raised in 47 (94%) cases. Mean aspartate aminotransferase (AST) was 98.77 U/L, mean alanine aminotransferase (ALT) was 88.09 U/L. In 46 (92%) cases AST was more than ALT. Enzyme rise was more in DHF (Grade III- mean AST 298 U/L, mean ALT 232 U/L, Grade II- mean AST 212.6 U/L, mean ALT 198.7 U/L, Grade I- mean AST 97.3 U/ L, mean ALT 86.2 U/L) than classical dengue fever (mean AST 61.7 U/L, mean ALT 54.9 U/L). Mean bilirubin was 1.82 mg/dl. No difference was observed between classical dengue fever and DHF regarding serum bilirubin level.Conclusion: The above results suggest that hepatic involvement in dengue fever is common and the amplitude of transaminase rise indicates the severity of the disease.Birdem Med J 2015; 5(2): 74-77